PENGARUH IKLIM ORGANISASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT. PELABUHAN INDONESIA II (PERSERO) CABANG PELABUHAN PONTIANAK - B1023131019, YULIYANTO (Jurnal Manajemen Update, 2017)
This study aims to examine and analyze the influence of organizational climate and work stress on employee performance PT. Pelabuhan Indonesia II (Persero) Branch Port of Pontianak. The population in this study are all permanent employees who work in PT. Pelabuhan Indonesia II (Persero) Branch Port of Pontianak. The sample in this research is 142 respondents by using sampling technique by using census method. Data analysis model used is Multiple Linear Regression Analysis. Based on the results of research indicates that organizational climate and work stress simultaneously affect the employee performance, this is evidenced by the F test that shows the significance value of 0.014 is smaller than 0.05. The result of t-test of organizational climate variables have a significant effect on employee performance, while work stress has no significant effect, it is proved that the value of significance is less than 0,05 that is 0,0011 for organizational climate, and 0,258 for work stress..Â Keywords : organization climate, work stress, and employees performance